Evolutionary Traits and Genomic Surveillance of SARS-CoV-2 in South America - Pablo A. Ortiz-Pineda; Carlos H. Sierra-Torres (Global Health, Epidemiology and Genomics)
Since the zoonotic event from which SARS-CoV-2 started infecting humans late in 2019, the virus has caused more than 5 million deaths and has infected over 500 million people around the world. The pandemic has had a severe impact on social and economic activities, with greater repercussions in low-income countries. South America, with almost 5% of the world’s population, has reckoned with almost a fifth of the total people infected and more than 26% (>1/4) of the deceased. Fortunately, the full genome structure and sequence of SARS-CoV-2 have been rapidly obtained and studied thanks to all the scientific efforts and data sharing around the world. Such molecular analysis of SARS-CoV-2 dynamics showed that rates of mutation, similar to other members of the Coronaviridae family, along with natural selection forces, could result in the emergence of new variants; few of them might be of high consequence. However, this is a serious threat to controlling the pandemic and, of course, enduring the process of returning to normalization with the implicit monetary cost of such a contingency. The lack of updated knowledge in South America justifies the need to develop a structured genomic surveillance program of current and emerging SARS-CoV-2 variants. The modeling of the molecular events and microevolution of the virus will contribute to making better decisions on public health management of the pandemic and developing accurate treatments and more efficient vaccines.